Retracted: Can the transtheoretical model motivate patients with coronary heart disease to exercise?. (4th June 2014) - Zhu, Li‐Xia; Ho, Shuk‐Ching; Sit, Janet WH; He, Hong‐Gu
<x xml:space="preserve">Abstract</x> Li‐Xia Zhu, Shuk‐Ching Ho, Janet WH Sit and Hong‐Gu He The above article from Nursing & Health Sciences, "Can the transtheoretical model motivate patients with coronary heart disease to exercise?" by Li‐Xia Zhu, Shuk‐Ching Ho, Janet WH Sit and Hong‐Gu He, published online on 4th June 2014 on Wiley Online Library (wileyonlinlibrary.com) DOI: 10.1111/nhs.12150, has been retracted by agreement between the lead author, the journal's Editor in Chief, Teresa Stone, and Wiley Publishing Asia Pty Ltd. The retraction has been agreed due to the main study having been previously published. References to the previously published articles: <mixed-citation id="nhs12150-cit-0001" publication-type="journal" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <string-name> <surname>Zhu</surname> <given-names>L‐X</given-names> </string-name>, <string-name><surname>Ho</surname><given-names>S‐C</given-names></string-name>, <string-name><surname>Sit</surname><given-names>JWH</given-names></string-name>, <string-name><surname>He</surname><given-names>H‐G</given-names></string-name>. The effects of a transtheoretical model‐based exercise stage‐matched intervention on exercise behavior in patients with coronary heart disease: A randomized controlled trial . <source content-type="journalTitle">Patient Educ. Couns.</source><year>2014</year>; <volume>95</volume>: <fpage>384</fpage>–<lpage>392</lpage>. http://www.pec‐journal.com/article/S0738‐3991(14)00129‐3/abstract</mixed-citation> <mixed-citation id="nhs12150-cit-0002" publication-type="journal" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <string-name> <surname>Zhu</surname> <given-names>L‐X</given-names> </string-name>, <string-name><surname>Ho</surname><given-names>S‐C</given-names></string-name>, <string-name><surname>Sit</surname><given-names>JWH</given-names></string-name>, <string-name><surname>He</surname><given-names>H‐G.</given-names></string-name> Effects of a transtheoretical model–based exercise stage–matched intervention on exercise behaviour and quality of life in patients with coronary heart disease: a randomized controlled trial . <source content-type="journalTitle">J. Adv. Nurs.</source><year>2014</year>. doi:10.1111/jan.12469http://onlinelibrary.wiley.com/doi/10.1111/jan.12469/abstract</mixed-citation> <mixed-citation id="nhs12150-cit-0003" publication-type="journal" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <string-name> <surname>Zhu</surname> <given-names>L‐X</given-names> </string-name>, <string-name><surname>Ho</surname><given-names>S‐C</given-names></string-name>, <string-name><surname>Sit</surname><given-names>JWH</given-names></string-name>, <string-name><surname>He</surname><given-names>H‐G</given-names></string-name>. Effect of a transtheoretical model‐based stage‐matched exercise intervention on exercise behavior and angina in patients with coronary heart disease: a randomized controlled trial . <source content-type="journalTitle">J. Cardiovasc. Nurs.</source><year>2014</year>. DOI: 10.1097/JCN.0000000000000162. http://journals.lww.com/jcnjournal/Citation/publishahead/Effect_of_a_Transtheoretical_Model_Based.99700.aspx</mixed-citation>